Distinguishing the chemical moiety of phosphoenolpyruvate that contributes to allostery in muscle pyruvate kinase - Urness, James M. (2012)
A series of substrate analogues has been used determine which chemical moieties of the substrate, phosphoenolpyruvate (PEP) contribute to the allosteric inhibition of rabbit muscle pyruvate kinase (M(1)-PYK) by phenylalanine. Replacing the carboxyl group of the substrate with a methyl alcohol, or removing the phosphate altogether, greatly reduces substrate affinity. However, removal of the carboxyl group is the only modification tested that removes the ability to allosterically reduce Phe binding. From this, it can be concluded that the carboxyl group of PEP is responsible for energetic coupling with Phe binding in the allosteric sites.